DISAIN TEKNOLOGI PANEN HUJAN UNTUK KEBUTUHAN RUMAHTANGGA: Studi Kasus di Daerah Istimewa Yogyakarta dan Nusa Tenggara Barat - Nani Heryani; Kurmen Sudarman; Sidiq H Talaohu; Sawiyo ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACT The Design of Rain Harvesting Technologies for Household Use: a Case Study in Yogyakarta Special Regionn and West Nusa Tenggara. Many parts of the world, including Indonesia, has been facing water shortage problems while water demand continues to grow. Rainfall harvesting could change the utilization pattern of rainfall by spatially and temporally, which would supply humankind with steady water sources. Characterized by simple operation, rainwater-harvesting techniques for domestics purposes have a great potential to be used also for irrigations. Rainfall harvesting could be conserved of water use from other water resources, while water use efficiency could be increased. The experiments were conducted at Selopamioro Village (Special Region of Yogyakarta ) and Banyu Urip Village (West Nusa Tenggara) in 2009 and 2011, respectively. The aims of the experiments were to develop rainfall harvesting technology and to design the criteria of techniques of rainfall harvesting the houshold purposes. The experiments were conducted through several steps as follow: (i) characterization of the area of experiments through rainfall and climate data collections during the last 10 years, the number of family members of the water users, water consumption/person/day, (ii) the installation of water storage tanks and distribution of pipes, and, (iii) data analysis of the potential of rainwater that could be harvested and the determination of the storage tank capacity. Results of the experiments showed that the potential of water that could be harvested at two sample houses in Selopamioro were 5.,8 and 78.5 m3/year respectively, while in three sample houses in Lombok were 74.2; 25.4 and 41.6 m3/year respectively. To meet the needs of water during the dry season, the maximum capacity of the reservoir should be made at two sample houses in Selopamioro were 19.5 and 28.4 m3 respectively, while those at three sample houses in Lombok were 37.06; 8.40 and 20.08 m3 respectively. Keywords : Design criteria, rainfall harvesting, household, droughtABSTRAK Sejak beberapa dekade terakhir di beberapa negara, termasuk Indonesia, sering terjadi kekeringan. Sementara kebutuhan air cenderung semakin meningkat. Panen hujan dapat mengubah pola pemanfaatan curah hujan secara spasial maupun temporal untuk memenuhi kebutuhan rumah tangga dengan sumber air relatif tetap. Dengan metode sederhana, teknik panen hujan disamping untuk memenuhi kebutuhan rumah tangga, juga dapat digunakan untuk irigasi. Penelitian dilaksanakan di Desa Selopamioro (Daerah Istimewa Yogyakarta) dan Desa Banyu Urip (Nusa Tenggara Barat) berturut-turut pada tahun 2009 dan 2011. Tujuan penelitian untuk mengembangkan teknologi panen hujan dan merancang kriteria panen hujan untuk kebutuhan rumahtangga. Penelitian dilakukan melalui beberapa tahapan yaitu (i) karakterisasi wilayah penelitian melalui pengumpulan data curah hujan dan iklim 10 tahun terakhir, jumlah anggota keluarga pengguna air, konsumsi air untuk kebutuhan rumah tangga/orang/hari, (ii) instalasi/pembuatan bangunan panen hujan berupa tangki penampung air dan pipa pendistribusiannya, dan (iii) analisis data meliputi potensi air hujan yang dapat dipanen dan penentuan kapasitas penampung air. Hasil penelitian menunjukkan bahwa potensi air yang dapat dipanen di dua rumah contoh di Selopamioro berturut-turut 53,8 dan 78,5 m3/tahun, sedangkan di tiga rumah contoh di Lombok berturut-turut 74,2; 25,4 dan 41,6 m3/tahun. Untuk memenuhi kebutuhan air selama musim kemarau, kapasitas maksimum tampungan yang harus dibuat di dua rumah contoh di Selopamioro berturut-turut 19,5 dan 28,4 m3, sedangkan di tiga rumah contoh di Lombok berturut-turut 37,06; 8,40 dan 20,08 m3. Kata kunci : Rancang bangun, panen hujan, rumah tangga, kekeringan